Neonatal spinal muscular atrophy with diaphragmatic paralysis is unlinked to 5q11.2-q13. Issue 3 (March 1995) - Novelli, G; Capon, F; Tamisari, L; Grandi, E; Angelini, C; Guerrini, P; Dallapiccola, B
Abstract : Two sibs affected by the severe neonatal form of spinal muscular atrophy (SMA) with diaphragmatic paralysis are described. The two sibs were discordant for the haplotypes determined by DNA markers flanking the SMA locus. This supports non-linkage of SMA to chromosome 5 in this family and indicates that the uncommon SMA type I variant associated with early onset respiratory failure maps outside the 5q11.2-q13.3 region.